Dietary docosahexaenoic acid supplementation alters select physiological endocannabinoid-system metabolites in brain and plasma - JodiAnne T. Wood; John S. Williams; Lakshmipathi Pandarinathan; David R. Janero; Carol J. Lammi-Keefe; Alexandros Makriyannis (Journal of Lipid Research, 2010)
The endocannabinoid metabolome consists of a growing, (patho)physiologically important family of fatty-acid derived signaling lipids. Diet is a major source of fatty acid substrate for mammalian endocannabinoid biosynthesis. The principal long-chain PUFA found in mammalian brain, docosahexaenoic acid (DHA), supports neurological function, retinal development, and overall health. The extent to which dietary DHA supplementation influences endocannabinoid-related metabolites in brain, within the context of the circulating endocannabinoid profile, is currently unknown. We report the first lipidomic analysis of acute 2-week DHA dietary supplementation effects on the physiological state of 15 fatty-acid, N-acylethanolamine, and glycerol-ester endocannabinoid metabolome constituents in murine plasma and brain. The DHA-rich diet markedly elevated DHA, eicosapentaenoic acid, 2-eicosapentanoylglycerol (EPG), and docosahexanoylethanolamine in both compartments. Dietary DHA enhancement generally affected the synthesis of the N-acyl-ethanolamine and glycerol-ester metabolites to favor the docosahexaenoic and eicosapentaenoic vs. arachidonoyl and oleoyl homologs in both brain and plasma. The greater overall responsiveness of the endocannabinoid metabolome in plasma versus brain may reflect a more circumscribed homeostatic response range of brain lipids to dietary DHA supplementation. The ability of short-term DHA enhancement to modulate select constituents of the physiological brain and plasma endocannabinoid metabolomes carries metabolic and therapeutic implications.